Novel semi-solid battery and preparation method thereof
By forming a nano -grade sulfur -containing organic film on the surface of the composite positive chip of the semi -solid lithium -ion battery, the side reaction problem of solid electrolyte and electrolyte at high temperatures is solved, and the high temperature life and safety performance of the battery significantly improves the battery.
Patent Information
- Application Number
- CN202411507819.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The existing semi-solid lithium-ion batteries have a side reaction with the battery liquid at high temperatures, resulting in rapid attenuation of battery life.
A new type of electrolyte containing a sulfur -containing compound additive is used to form a nano -grade thick sulfur -containing organic film on the surface of the composite positive chip, which isolates the direct contact between the solid electrolyte and the electrolyte to avoid high temperature side reactions.
It significantly improves the service life of the battery under high temperature conditions, and improves the high temperature cycle stability and safety performance of the battery.
Smart Images

Figure CN119381518A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to the technical field of semi-solid lithium ion batteries containing novel electrolytes. Background Art
[0002] With the rapid development of digital products, electric vehicles, and energy storage industries, the requirements for energy density, long cycle life, and safety of lithium-ion batteries have also increased accordingly. Lithium secondary batteries based on liquid electrolytes are difficult to meet the above application requirements and have certain safety hazards. Therefore, solid electrolyte lithium-ion batteries, which have great advantages in battery energy density and safety, have developed rapidly.
[0003] Solid electrolytes are divided into polymer solid electrolytes, oxide solid electrolytes, sulfide solid electrolytes, etc. There are various ways to prepare solid batteries, such as forming composite electrode sheets by mixing or coating with positive and negative electrode materials, or coating on the surface of diaphragms or positive and negative electrode sheets to construct a thin electrolyte layer. They can also be prepared separately into electrolyte diaphragms to replace commercial diaphragms.
[0004] A new preparation method in the prior art is to directly coat a solid electrolyte layer on the surface of the electrode active material layer. The coating layer is thin, so it is more conducive to improving the battery performance. For example, Chinese patent application CN 116741942A discloses a lithium iron manganese phosphate (LFMP) composite positive electrode sheet, which is coated with a solid electrolyte layer on the surface of the active material layer, and solves the problem of Mn dissolution in the manganese-containing positive electrode material by physical barrier; Chinese patent application CN 117727864 A discloses a preparation method of a composite electrode sheet including a current collector, which is provided with a lithium supplement layer, an active layer and an electrolyte layer including a solid electrolyte and a ceramic coated on the surface of the solid electrolyte on at least one side of the current collector. This method solves the problems of low positive and negative electrode interface safety and low energy density of the battery in the existing battery.
[0005] Although the above existing products or methods can significantly improve the energy density and safety performance of batteries, they cannot solve the problem that the solid electrolyte coating is prone to react with the battery fluid at high temperatures, thus causing the battery life to decay rapidly. For example, the solid electrolyte LATP will react with the fluorine-containing components in the electrolyte at high temperatures to generate TiF3, which makes Ti 3+ It dissolves into the electrolyte, causing serious side reactions, resulting in a rapid decay of the high-temperature life of the semi-solid-state battery, which cannot meet application requirements. Summary of the invention
[0006] In view of the defects of the prior art, the purpose of the present invention is to provide a new semi-solid-state battery and a preparation method thereof. The semi-solid-state battery comprises a composite positive electrode sheet containing a solid electrolyte layer and an electrolyte containing a sulfur-containing cyclic compound additive. During the first charge and discharge process, the sulfur-containing cyclic compound additive can form a sulfur-containing organic film with a nanometer thickness on the surface of the solid electrolyte layer, effectively avoiding high-temperature side reactions between the solid electrolyte and the electrolyte during use, thereby greatly improving the service life of the battery under high temperature conditions.
[0007] The technical solution of the present invention is as follows:
[0008] A novel semi-solid battery, comprising a novel electrolyte and a semi-solid battery dry cell, wherein the semi-solid battery dry cell comprises a negative electrode sheet, a composite positive electrode sheet and a separator for separating the negative electrode sheet from the composite positive electrode sheet, wherein the composite positive electrode sheet comprises a current collector layer, an active material layer attached to the current collector layer and a solid electrolyte layer attached to the active material layer, wherein the novel electrolyte is a lithium-ion battery electrolyte with one or more of the following sulfur-containing cyclic compounds added thereto:
[0009]
[0010] The sulfur-containing cyclic compound in the novel electrolyte of the present invention can form a sulfur-containing organic interface layer on the surface of the solid electrolyte through an electrochemical decomposition reaction, which can effectively isolate the direct contact between the solid electrolyte and the electrolyte, effectively protect the electrode material of the battery, and improve the high-temperature cycle performance of the battery.
[0011] Preferably, the added mass of the sulfur-containing cyclic compound is 0.1 to 8% of the total mass of the novel electrolyte, and more preferably, 0.5 to 3%.
[0012] Preferably, the lithium-ion battery electrolyte comprises a lithium salt and an organic solvent, wherein the organic solvent is selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl acetate (MA), ethyl acetate (EA), ethyl propionate (EP), methyl propionate (MP), and propyl propionate (PP); the lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium bis(fluorosulfonyl imide) (LiFSI), lithium bis(trifluoromethylsulfonyl imide) (LiTFSI), lithium difluorooxalatoborate (LiODFB), lithium dioxalatoborate (LiBOB), and lithium tetrafluoroborate (LiBF4).
[0013] Preferably, the thickness of the solid electrolyte layer is 4-20 μm, more preferably, 6-12 μm.
[0014] Preferably, the positive active material included in the active material layer is selected from one or more of lithium nickel manganese cobalt oxide (NCM), lithium iron phosphate (LiFePO4), lithium manganese oxide (LiMn2O4), lithium cobalt oxide (LiCoO2), lithium iron manganese phosphate (LiFe x Mn (1-x) PO4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4), lithium-rich manganese-based (LMR); the solid electrolyte included in the solid electrolyte layer is selected from one or more of lithium aluminum titanium phosphate (LATP), lithium germanium aluminum phosphate (LAGP), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanium oxide (LLTO), lithium phosphorus oxynitride (LIPON). More preferably, the solid electrolyte is lithium aluminum titanium phosphate with the molecular formula Li Y Al X Ti 2-X (PO4)3, where 0 < X < 1 and 1 < Y.
[0015] Preferably, the negative electrode sheet contains one or more of the following negative active materials: graphite, soft carbon, hard carbon, metallic lithium, nano-silicon, nano-tin, silicon-carbon, silicon-oxygen, tin-carbon, and tin-oxygen.
[0016] The present invention further provides a method for preparing the above semi-solid state battery, which includes:
[0017] Mixing the positive active material, the first binder, the conductive agent, and the first solvent evenly to obtain a first slurry, coating it on at least one surface of the current collector, and then drying and rolling to obtain a basic positive electrode sheet;
[0018] Mixing the solid electrolyte, the second binder, the dispersant, and the second solvent evenly to obtain a second slurry, coating it on the basic positive electrode sheet by a doctor blade coating method, and then drying and rolling to obtain the composite positive electrode sheet;
[0019] Assembling and encapsulating the composite positive electrode sheet, the separator, and the negative electrode sheet to obtain the semi-solid state battery dry cell core;
[0020] Injecting the novel electrolyte into the semi-solid state battery dry cell core to obtain the semi-solid state battery.
[0021] Preferably, the mass of the solid electrolyte is 65% - 90% of the total mass of the second slurry, and more preferably, 75% - 85%; the injection mass of the novel electrolyte is 5% - 25% of the total mass of the semi-solid state battery, and more preferably, 10% - 15%.
[0022] Preferably, the first binder is selected from one or more of polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and polyacrylic acid (PAA).
[0023] Preferably, the conductive agent is selected from one or more of carbon black, Ketjen black, carbon tubes, carbon fibers, graphene, and conductive graphite.
[0024] Preferably, the second binder is selected from one or more of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), polyethylene oxide (PEO), and polyacrylonitrile (PAN), among which polyvinylidene fluoride (PVDF) is more preferred.
[0025] Preferably, the material of the diaphragm is selected from one or more of polyethylene (PE), polypropylene (PP), and polyimide (PI).
[0026] Preferably, the first solvent is selected from N-methyl-2-pyrrolidone (NMP).
[0027] Preferably, the second solvent is selected from propylene carbonate (PC).
[0028] In the semi-solid battery provided by the present invention, the electrolyte containing the sulfur cyclic compound additive can form a nanoscale protective film in situ on the surface of the composite positive electrode sheet, effectively improving the high-temperature stability of the oxide solid electrolyte. Compared with conventional liquid lithium-ion batteries, the semi-solid battery of the present invention can significantly improve the safety performance of lithium batteries, will not catch fire or explode when punctured, and has excellent high-temperature cycle stability, promoting the application and development of high-safety, high-specific energy, and high-temperature application lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the battery image after acupuncture in Example 1;
[0030] Figure 2 This is the battery image after acupuncture in Example 2;
[0031] Figure 3 The voltage-temperature variation curve of the acupuncture process in Example 2;
[0032] Figure 4 It is a comparison chart of the 60°C cycle life of Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0033] The present invention is described in detail below in conjunction with the embodiments and drawings, but it should be understood that the embodiments and drawings are only used to exemplify the present invention and do not constitute any limitation on the protection scope of the present invention. All reasonable changes and combinations within the scope of the inventive concept of the present invention fall within the protection scope of the present invention.
[0034] Example 1
[0035] The semi-solid-state battery was prepared by the following steps:
[0036] (1) Nickel manganese oxide lithium ternary active material (NCM622), PVDF, SP, and CNT were dispersed in NMP at a mass ratio of 97:1.2:1:0.8 to obtain a first slurry, which was coated on both sides of a 14 μm thick aluminum foil, followed by drying and rolling to obtain a double-sided surface density of 3.50 g / dm 2 The positive electrode;
[0037] (2) dispersing the solid electrolyte LATP, PVDF and dispersant in PC at a mass ratio of 90:9:1, stirring evenly to obtain a second slurry, applying the slurry on the positive electrode sheet by a doctor blade film forming method, and then drying and rolling to form a solid electrolyte layer with a thickness of 4 μm on the surface of the positive electrode sheet to obtain a composite positive electrode sheet;
[0038] (3) The negative electrode active materials graphite, SBR, SP, and CMC were dispersed in water at a mass ratio of 96:2:1:1 to obtain a negative electrode slurry, which was coated on both sides of a 9 μm thick copper foil, followed by drying and roll pressing to obtain a double-sided surface density of 1.84 g / dm 2 The negative electrode;
[0039] (4) The composite positive electrode sheet, commercial PE separator, and negative electrode sheet are assembled in a stacked form, and sealed and packaged with an aluminum-plastic film to form a 15Ah semi-solid battery dry cell to be injected with liquid;
[0040] (5) Ethylene carbonate and dimethyl carbonate were mixed uniformly in a mass ratio of 3:7, and LiPF6 was added in an amount of 12.8% of the total mass of the electrolyte, followed by adding a sulfur-containing cyclic compound additive represented by formula 2 in an amount of 2% of the total mass of the electrolyte to obtain an electrolyte E1;
[0041] (6) Injecting the electrolyte E1 into the semi-solid-state battery dry cell, and then undergoing aging, formation, aging, secondary sealing, and capacity separation processes to obtain a finished semi-solid-state battery.
[0042] Example 2
[0043] A semi-solid battery was prepared according to the process of Example 1, except that the thickness of the solid electrolyte layer was 8 μm.
[0044] Example 3
[0045] A semi-solid-state battery was prepared according to the process of Example 1, except that the thickness of the solid electrolyte layer was 17 μm.
[0046] Example 4
[0047] A semi-solid-state battery was prepared according to the process of Example 1, except that the solid electrolyte was LLZO and the thickness of the solid electrolyte layer was 17 μm.
[0048] Example 5
[0049] A semi-solid-state battery was prepared according to the process of Example 1, except that the solid electrolyte was LLTO and the thickness of the solid electrolyte layer was 8 μm.
[0050] Example 6
[0051] A semi-solid-state battery was prepared according to the process of Example 2, with the only difference being that the electrolyte used was a mixture of ethylene carbonate and dimethyl carbonate in a mass ratio of 3:7, followed by the addition of LiPF6 in an amount of 12.8% of the total mass of the electrolyte, and then the addition of a sulfur-containing cyclic compound additive represented by formula 6 in an amount of 2% of the total mass of the electrolyte to obtain electrolyte E2.
[0052] Example 7
[0053] A semi-solid-state battery was prepared according to the process of Example 2, with the only difference being that the electrolyte used was a mixture of ethylene carbonate and dimethyl carbonate in a mass ratio of 3:7, followed by the addition of LiPF6 in an amount of 12.8% of the total mass of the electrolyte, and then the addition of a sulfur-containing cyclic compound additive represented by formula 7 in an amount of 2% of the total mass of the electrolyte to obtain electrolyte E3.
[0054] Example 8
[0055] A semi-solid-state battery was prepared according to the process of Example 2, with the only difference being that the electrolyte used was a mixture of ethylene carbonate and dimethyl carbonate in a mass ratio of 3:7, followed by the addition of LiPF6 in an amount of 12.8% of the total mass of the electrolyte, and then the addition of a sulfur-containing cyclic compound additive shown in Formula 8 in an amount of 2% of the total mass of the electrolyte to obtain electrolyte E4.
[0056] Example 9
[0057] A semi-solid-state battery was prepared according to the process of Example 2, with the only difference being that the electrolyte used was a mixture of ethylene carbonate and dimethyl carbonate in a mass ratio of 3:7, followed by the addition of LiPF6 in an amount of 12.8% of the total mass of the electrolyte, and then the addition of a sulfur-containing cyclic compound additive shown in Formula 2 in an amount of 5% of the total mass of the electrolyte to obtain electrolyte E5.
[0058] Comparative Example 1
[0059] A lithium-ion battery is prepared by the following steps:
[0060] (1) Nickel manganese oxide lithium ternary active material (NCM622), PVDF, SP, and CNT were dispersed in NMP at a mass ratio of 97:1.2:1:0.8 to obtain a first slurry, which was coated on both sides of a 14 μm thick aluminum foil, followed by drying and rolling to obtain a double-sided surface density of 3.50 g / dm 2 The positive electrode;
[0061] (2) The negative electrode active materials graphite, SBR, SP, and CMC were dispersed in water at a mass ratio of 96:2:1:1 to obtain a negative electrode slurry, which was coated on both sides of a 9 μm thick copper foil, followed by drying and roll pressing to obtain a double-sided surface density of 1.84 g / dm 2 The negative electrode;
[0062] (3) assembling the obtained positive electrode sheet, commercial PE separator, and negative electrode sheet in a stacked form, and sealing and packaging them with aluminum-plastic film to form a 15Ah lithium battery dry cell to be injected with liquid;
[0063] (4) Ethylene carbonate and dimethyl carbonate were mixed uniformly in a mass ratio of 3:7, and LiPF6 was added in an amount of 12.8% of the total mass of the electrolyte to obtain an electrolyte E0;
[0064] (5) Injecting the electrolyte E0 into the semi-solid battery dry cell, and then obtaining the finished lithium-ion battery through aging, formation, aging, secondary sealing, and capacity division processes.
[0065] Comparative Example 2
[0066] A lithium ion battery was prepared according to the process of Example 2, except that the electrolyte used was the same electrolyte E0 as that of Comparative Example 1.
[0067] Comparative Example 3
[0068] A lithium ion battery was prepared according to the process of Comparative Example 1, except that the electrolyte used was the electrolyte E1 consistent with that of Example 1.
[0069] The semi-solid batteries or lithium-ion batteries prepared in the above embodiments and comparative examples are subjected to performance tests, including:
[0070] Impedance test: The battery was charged to 50% SOC at 0.2C current at room temperature, with a cut-off current of 0.05C, and left to stand for 1h. The battery impedance was tested and fitted using an electrochemical workstation.
[0071] 60℃ cycle test: In a 60℃ constant temperature box, the battery is repeatedly charged and discharged in the capacity range of 0-100% SOC with a charge and discharge current of 1C / 1C, and the charge and discharge capacity of each cycle is recorded. A 0.2C / 0.2C (0-100% SOC) charge and discharge test is performed every 100 cycles to monitor the capacity retention rate of the battery. The test is stopped when the capacity decays to 80% HOC.
[0072] Acupuncture safety testing, including:
[0073] (1) Charge to full voltage at 0.2C, select CC-CV mode, cut-off current 0.01C, and leave for 4 hours;
[0074] (2) At room temperature, place the battery in an explosion-proof box with the center of the largest surface of the battery aligned with the steel needle;
[0075] (3) Place at least one temperature test device at 1 cm from the battery penetration point and 1 cm from the battery edge to test the battery temperature online;
[0076] (4) Connect the voltage test device and test the voltage online;
[0077] (5) Use a φ5mm high-temperature resistant steel needle with a cone angle of 45° and a smooth surface without rust, oxide layer or oil at a speed of 25±5mm / s to penetrate the battery from a direction perpendicular to the largest surface of the battery. The penetration position is the geometric center of the largest surface of the battery, and the steel needle stays in the battery;
[0078] (6) Observe for 1 hour and record the test process video and the battery surface temperature and voltage change data.
[0079] The test results are shown in Table 1 below:
[0080] Table 1 Battery performance test results
[0081]
[0082] Some exemplary images from the above tests are shown in the attached Figure 1-4 As shown, Figure 1 This is the battery image after acupuncture in Example 1; Figure 2 This is the battery image after acupuncture in Example 2; Figure 3 The voltage-temperature variation curve of the acupuncture process in Example 2; Figure 4 It is a comparison chart of the 60°C cycle life of Example 1 and Comparative Example 2.
[0083] It can be seen from the above test results that, according to the comparison between Example 2, Comparative Example 1 and Comparative Example 2, the semi-solid battery assembled with the LATP solid electrolyte layer and the conventional electrolyte E0 improves the battery safety performance (no fire when punctured), but will significantly deteriorate its high temperature 60°C cycle life; while the semi-solid battery assembled with the LATP solid electrolyte layer and the sulfur-containing cyclic compound additive electrolyte E1 can not only ensure the safety performance of the battery, but also significantly improve its high temperature life.
[0084] According to the comparison of Examples 1, 2, and 3, if the thickness of the solid electrolyte layer is too thin, it cannot effectively physically isolate the positive and negative electrodes, and safety cannot be guaranteed. If the solid electrolyte layer is too thick, it will increase the battery impedance and deteriorate its high temperature 60°C cycle life. Therefore, the optimal coating thickness of the solid electrolyte layer should be around 6 to 12 μm.
[0085] According to the comparison of Examples 2, 4, and 5, different oxide solid electrolytes have good compatibility with the sulfur-containing cyclic compound additive electrolyte E1.
[0086] According to the comparison of Examples 2, 6, 7, and 8, the same oxide solid electrolyte has good compatibility with sulfur-containing cyclic compound additives of different structures.
[0087] According to the comparison between Examples 2 and 9, as the content of the sulfur-containing cyclic compound additive increases, the effect of further improving the high-temperature cycle life of the battery is not obvious, but the battery impedance increases significantly.
[0088] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A novel semi-solid battery, comprising a novel electrolyte and a semi-solid battery dry cell, wherein the semi-solid battery dry cell comprises a negative electrode sheet, a composite positive electrode sheet and a separator for separating the negative electrode sheet from the composite positive electrode sheet, wherein the composite positive electrode sheet comprises a current collector layer, an active material layer attached to the current collector layer and a solid electrolyte layer attached to the active material layer; the novel electrolyte is a lithium-ion battery electrolyte with one or more of the following sulfur-containing cyclic compounds added thereto:
2. The novel semi-solid-state battery according to claim 1, characterized in that: The added mass of the sulfur-containing cyclic compound is 0.1-8% of the total mass of the novel electrolyte, preferably 0.5-3%.
3. The novel semi-solid-state battery according to claim 1, characterized in that: The lithium ion battery electrolyte comprises a lithium salt and an organic solvent, wherein the organic solvent is selected from one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl acetate, ethyl acetate, ethyl propionate, methyl propionate, and propyl propionate; and the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium perchlorate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium difluorooxalatoborate, lithium dioxalatoborate, and lithium tetrafluoroborate.
4. The novel semi-solid-state battery according to claim 1, characterized in that: The thickness of the solid electrolyte layer is 4-20 μm, preferably 6-12 μm.
5. The novel semi-solid-state battery according to claim 1, characterized in that: in, The positive electrode active material included in the active material layer is selected from one or more of lithium nickel manganese oxide ternary materials, lithium iron phosphate, lithium manganate, lithium cobaltate, lithium iron manganese phosphate, lithium nickel manganate, and lithium-rich manganese-based materials; the solid electrolyte included in the solid electrolyte layer is selected from one or more of lithium titanium aluminum phosphate, lithium germanium aluminum phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, and lithium phosphorus oxynitride. Preferably, the solid electrolyte is selected from lithium titanium aluminum phosphate with the molecular formula Li Y Al X Ti 2-X (PO4)3, where 0 < X < 1 and 1 < Y.
6. The novel semi-solid-state battery according to claim 1, characterized in that: The negative electrode sheet contains one or more of the following negative electrode active materials: graphite, soft carbon, hard carbon, metallic lithium, nano silicon, nano tin, silicon carbon, silicon oxygen, tin carbon and tin oxygen.
7. The method for preparing a novel semi-solid-state battery according to any one of claims 1 to 6, characterized in that: It includes: (1) mixing the positive electrode active material, the first binder, the conductive agent and the first solvent uniformly to obtain a first slurry, coating the first slurry on at least one side of the current collector, and then drying and rolling to obtain a basic positive electrode sheet; (2) mixing the solid electrolyte, the second binder, the dispersant and the second solvent uniformly to obtain a second slurry, coating the second slurry on the base positive electrode sheet by a doctor blade coating method, and then drying and rolling to obtain the composite positive electrode sheet; (3) Assembling and encapsulating the composite positive electrode sheet, the separator and the negative electrode sheet to obtain the semi-solid-state battery dry cell; (4) Injecting the novel electrolyte into the semi-solid-state battery dry cell to obtain the semi-solid-state battery.
8. The preparation method according to claim 7, characterized in that: in, The mass of the solid electrolyte is 65% to 90% of the total mass of the second slurry, preferably 75% to 85%; the injected mass of the novel electrolyte is 5 to 25% of the total mass of the semi-solid battery, preferably 10 to 15%.
9. The preparation method according to claim 7, characterized in that: in, The first binder is selected from one or more of polyvinylidene fluoride, polymethyl methacrylate, polyacrylonitrile, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyacrylic acid; and / or, the conductive agent is selected from one or more of carbon black, Ketjen black, carbon tube, carbon fiber, graphene, and conductive graphite; and / or, the second binder is selected from one or more of polyvinylidene fluoride, polyacrylic acid, polyethylene oxide, and polyacrylonitrile; and / or, the material of the diaphragm is selected from one or more of polyethylene, polypropylene, and polyimide; and / or, the first solvent is selected from N-methyl-2-pyrrolidone; and / or, the second solvent is selected from propylene carbonate.
Citation Information
Patent Citations
Composite positive plate as well as preparation method and application thereof
CN116741942A
Composite electrode plate, preparation method and battery
CN117727864A
Electrolyte and lithium ion battery
CN113258136A
Electrode plate of liquid battery, preparation method and lithium ion battery
CN118263394A
Lithium ion secondary battery
CN118676423A
Cited By
Chalcogenide cyclic compound as well as preparation method and application thereof
CN121021575A
Lithium ion battery electrolyte based on chalcogenide cyclic compound, preparation method of lithium ion battery electrolyte and ternary lithium ion battery
CN121035340A
Electrolyte of lithium iron phosphate ion battery, preparation method of electrolyte and lithium iron phosphate ion battery
CN121054805A
Chalcogenide bicyclic compound as well as preparation method and application thereof
CN121135781A
Sulfonate compound as well as preparation method and application thereof
CN121824366A